Changes in traditional medical education programs and obstacles to be overcome to achieve the teaching of Integrative Medicine - Campos Rey de Castro, Jorge (1968)
The historical reasons , training of medical teachers and current organizational structures in which education is given, which are obstacles to change the traditional orientation of medical education which is still being imparted in most analyzes medical schools . To form a new type of doctor who is able to exert integrative medicine and act as leader of his own community within their specific field , in the difficult path to achieve development , a prerequisite is retrain the current professors of medicine , switch structures of organisms in which education is provided and ensure close coordination between universities and state agencies responsible for public health , and, therefore, are those who, as employers, to absorb most professional forming medical schools . The people in intercultural situation , claim to be attended by health professionals to be trained with a different philosophy and methods that have been traditionally used in medical schools inspired by classic molds imported from the metropolis.